Efficient biocatalysis in organic media with hemoglobin and poly(acrylic acid) nanogels - Zore, Omkar V (Langmuir : the ACS journal of surfaces and colloids, 2014)
We previously reported that the stability and aqueous catalytic activity of met-hemoglobin (Hb) was improved when covalently conjugated with poly(acrylic acid) (PAA). In the current study, the Hb-PAA-water interface was modified to improve Hb catalytic efficiency in organic solvents (0-80% v/v organic solvent; remainder is the conjugate, the substrate, and water). The protein-polymer-solvent interface modification was achieved by esterifying the carboxylic acid groups of Hb-PAA with ethanol (EtOH) or 1-propanol (1-prop) after activation with carbodiimide. The resulting esters (Hb-PAA-Eth and Hb-PAA-1-prop, respectively) showed high peroxidase-like catalytic activities in acetonitrile (ACN), dimethylformamide (DMF), EtOH, and methanol (MeOH). Catalytic activities depended on the log(P) values of the solvents, which is a measure of solvent lipophilicity. The highest weighted-average activities were noted in MeOH for all three conjugates, and the lowest average activities were noted in DMF for two of the conjugates. Interestingly, the average activities of the conjugates were higher than that of Hb in all solvents except in ACN. The ratio of the catalytic rate constant (kcat) to the Michaelis constant (KM), the catalytic efficiency, for Hb-PAA-Eth in MeOH was the highest noted, and it is ~3-fold higher than that of Hb in buffer; conjugates offered higher efficiencies than Hb at most solvent compositions. This is the very first general, versatile, modular strategy of coupling the enhanced stability of Hb with improved activity in organic solvents via the chemical manipulation of the polymer shell around Hb and provides a robust approach to efficient biocatalysis in organic solvents